Bereavement, complicated grief, and the rationale for diagnosis in psychiatry - Pies, Ronald (Les Laboratoires Servier, 2012)
Recent controversies over the DSM-5 raise a foundational question for all diagnostic classifications: what is their underlying purpose? The author raises this question in the context of the proposed elimination of the “bereavement exclusion” from the DSM-5; and the possible addition of the category called “Complicated Grief.” The author argues that our psychiatric diagnostic scheme should not be aimed primarily at establishing boundaries among putative “natural types.” Rather, it ought to be guided by the principle of “instrumental validity, ” which focuses on reducing the suffering and incapacity of those who seek our care. In so far as the category of “Complicated Grief” helps achieve this goal, it will foster the humane and ethical values that underlie medical practice.